2015
DOI: 10.1099/jmm.0.000125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibiotics on biofilm and unattached cells of a clinical Staphylococcus aureus isolate from bone and joint infection

Abstract: Treatment of orthopaedic infections remains challenging owing to the inability of antibiotics to eradicate biofilms and prevent their regrowth. The present study characterized the effects of 12 antibiotics on in vitro biofilm formed by a representative strain of meticillin-susceptible Staphylococcus aureus (MSSA) isolated from a bone infection. Determination of the minimum biofilm eradication concentrations indicated that in vitro eradication of 24 h-old biofilms required concentrations up to 51 200 times high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 21 publications
(21 reference statements)
1
25
0
1
Order By: Relevance
“…The S. aureus LYO-S2 mCherry-tagged strain was constructed after insertion of pAH9 plasmid [22] into the LYO-S2 clinical strain [23] by electroporation, as described previously [24]. The S. aureus LYO-S2 mCherrytagged fluorescent strain, named S. aureus mCherry-LYO-S2, was selected onto Luria-Bertani (LB) agar containing erythromycin (10 μg/mL).…”
Section: Mcherry-tagged Strain Constructionmentioning
confidence: 99%
“…The S. aureus LYO-S2 mCherry-tagged strain was constructed after insertion of pAH9 plasmid [22] into the LYO-S2 clinical strain [23] by electroporation, as described previously [24]. The S. aureus LYO-S2 mCherrytagged fluorescent strain, named S. aureus mCherry-LYO-S2, was selected onto Luria-Bertani (LB) agar containing erythromycin (10 μg/mL).…”
Section: Mcherry-tagged Strain Constructionmentioning
confidence: 99%
“…The patient underwent three antibiotic treatments over 147 days including fosfomycin combined with oxacillin for 55 days in the middle of the treatment period. The outcome was favorable after 3-year clinical follow-up.We previously demonstrated this strain's ability to form biofilm in vitro, and the in vitro anti-biofilm activity of fosfomycin at sub-MICs(4). We also showed that the effective concentrations of fosfomycin required for 24h-old biofilm eradication were unattainable by conventional antibiotic administration(4).…”
mentioning
confidence: 94%
“…The outcome was favorable after 3-year clinical follow-up.We previously demonstrated this strain's ability to form biofilm in vitro, and the in vitro anti-biofilm activity of fosfomycin at sub-MICs(4). We also showed that the effective concentrations of fosfomycin required for 24h-old biofilm eradication were unattainable by conventional antibiotic administration(4). We therefore used S. aureus LYO-S2 as the model strain to study the molecular effects of fosfomycin on sessile cells using RNA-seq technology with both biofilm cells formed for 4h in the presence of fosfomycin at sub-MIC and pre-formed 24h-old biofilm cells later treated with sub-MBEC of fosfomycin for 24 hours.…”
mentioning
confidence: 95%
See 2 more Smart Citations